2016
DOI: 10.1002/pen.24342
|View full text |Cite
|
Sign up to set email alerts
|

General model for comparative tensile mechanical properties of composites fabricated from fly ash and virgin/recycled high-density polyethylene

Abstract: The present work on the mechanical properties of 10 wt% fly ash additions in 2.5 wt% increments to recycled high-density polyethylene (RHDPE) synthesizes experimental data from three similar published reports. The present work shows, as a function of increasing fly ash addition level, maxima at the initial fly ash addition level of 2.5 wt% for the tensile elastic modulus (125%) and tensile strength (110%); a slight general increase in the yield stress (16%); and significant general decreases in the yield strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 72 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…This behavior confirms improved interfacial adhesion between r‐PVC and FA (Si) in presence of ESO due to H‐bonding and dipole–dipole interaction as explained earlier. The r‐PVC/FA (Si‐5) composites exhibited optimum hardness of 99 which is 52.3% higher than the untreated counterpart 34 …”
Section: Resultsmentioning
confidence: 99%
“…This behavior confirms improved interfacial adhesion between r‐PVC and FA (Si) in presence of ESO due to H‐bonding and dipole–dipole interaction as explained earlier. The r‐PVC/FA (Si‐5) composites exhibited optimum hardness of 99 which is 52.3% higher than the untreated counterpart 34 …”
Section: Resultsmentioning
confidence: 99%
“…The interest of using fly ash in different applications is evident because of its many advantages; such as low density, low cost, smooth spherical surface, well distributed internal stresses, and good processability of the filled materials . Although many researchers have recognized the reinforcing effect of fly ash for polymers , few publications focused on the fly ash composites performance dependency on its particle size. Kulkarni et al reported that the performance of cenosphere/ABS composites is a function of fly ash particle size.…”
Section: Introductionmentioning
confidence: 99%
“…The active utilization of waste materials for producing economic and efficient products is one of the supreme research areas worldwide . In the quest of regulating the waste management and sustainability, production of polymer composites with the inclusion of various waste materials as filler is conceptually a modest and often cost‐effective tactics.…”
Section: Introductionmentioning
confidence: 99%